2022
DOI: 10.1097/mcp.0000000000000901
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the management of systemic sclerosis-associated interstitial lung disease

Abstract: Purpose of reviewInterstitial lung disease associated with systemic sclerosis (SSc-ILD) is a frequent organ manifestation leading to high morbidity and mortality. In 2020, the European management recommendations for SSc-ILD were published. Despite being comprehensive, several questions could not be answered or no consensus was reached.Recent findingsWe highlight recent advances in the screening and early diagnosis, including surveys emphasizing that still 30–40% of all experts do not order baseline HRCTs in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 38 publications
0
1
0
1
Order By: Relevance
“…Zu berücksichtigen sind die Charakteristika der Studienpopulation: kurze Krankheitsdauer, progressive Erkrankung, erhöhte humorale Entzündungsaktivität. Mit dem stetig wachsenden Verständnis der zugrundeliegenden Pathophysiologie wächst auch die Zahl der klinischen Phase-II/Phase-III-Studien für SSc-ILD (Review in [73]).…”
Section: Therapeutisches Managementunclassified
“…Zu berücksichtigen sind die Charakteristika der Studienpopulation: kurze Krankheitsdauer, progressive Erkrankung, erhöhte humorale Entzündungsaktivität. Mit dem stetig wachsenden Verständnis der zugrundeliegenden Pathophysiologie wächst auch die Zahl der klinischen Phase-II/Phase-III-Studien für SSc-ILD (Review in [73]).…”
Section: Therapeutisches Managementunclassified
“…Although SSc-related ILD continues to be associated with a high mortality, over the past 15 years there have been advances in treatment that can slow progression. 66 Recent review articles on SSc-related ILD provide more detail, [67][68][69][70] but key findings relevant to changing clinical practice are summarized here. Two randomized placebo-controlled trials reported in 2006 suggested benefit from cyclophosphamide.…”
Section: Advances In Managementmentioning
confidence: 99%